2017
DOI: 10.1136/bmjgh-2017-000301
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the challenges to caring for low birthweight babies in rural southern Malawi: a qualitative study exploring caregiver and health worker perceptions and experiences

Abstract: BackgroundLow birthweight (LBW) babies account for >80% of neonatal mortality in sub-Saharan Africa and South Asia and those who survive the neonatal period are still at risk of detrimental outcomes. LBW is a major public health problem in Malawi and strongly contributes to the country’s high neonatal mortality rate. We aimed to get a better understanding of the care of LBW babies in rural Malawi in order to inform action to improve their outcomes.MethodsQualitative methods were used to identify challenges fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 29 publications
8
25
0
Order By: Relevance
“…The commonly perceived causes of LBW included maternal inadequate diet, poor nutrition, and illness in pregnancy, premature delivery, and twin births, which are in line with the findings of previous research in similar settings [29, 36]. This suggests that most women and their families were aware of several important risk factors of the newborn’s poor birthweight, however, there were several other causes reported which may put their newborn’s health at risk by limiting the preventive practices of LBW.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The commonly perceived causes of LBW included maternal inadequate diet, poor nutrition, and illness in pregnancy, premature delivery, and twin births, which are in line with the findings of previous research in similar settings [29, 36]. This suggests that most women and their families were aware of several important risk factors of the newborn’s poor birthweight, however, there were several other causes reported which may put their newborn’s health at risk by limiting the preventive practices of LBW.…”
Section: Discussionsupporting
confidence: 85%
“…This suggests that most women and their families were aware of several important risk factors of the newborn’s poor birthweight, however, there were several other causes reported which may put their newborn’s health at risk by limiting the preventive practices of LBW. For instance, the influence of supernatural spirit was sometimes cited as a cause of giving birth to a LBW newborn which is consistent with a few prior studies [29, 34]. This belief sometimes prevents pregnant women from seeking antenatal care as they remain at home and avoid travelling to the hospital to keep themselves safe from the bad spirit [37].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Videos and mobile phone apps addressing parental issues in local languages may be additional aids, and some are already available (in Kinyarwanda in Rwanda 19 ). Developing close links with community health workers is likely to be advantagous 20 ; an extensive network of volunteer community health workers has been developed in Rwanda, though additional training in the care of the preterm or ill infants graduating from the neonatal unit may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…[5,14] Koenraads et al in Southern Malawi reported high burden of care, feeding problems, and discrimination/stigma as burdens for caregivers, stated as: "Taking care of a small baby is a problem. [14] For instance I did not have time to do other work except concentrating on exclusive breastfeeding… though with scarcity of food in the house from morning to evening this life seems tough," "When he was born the breastmilk was not coming out, I tried forcing him to suck, but his jaws were not ready," and "When they see us they point fingers at us…." It should stand to reason that these reported burdensome experiences could worsen when dealing with a sick baby in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%